Physicochemical and ecotoxicological based assessment of bottom sediments from the Luján River basin, Buenos Aires, Argentina - Peluso, María Leticia (2013)
The physicochemical analysis of bottom sediments of the Lujan River was done on samples from 14 sites situated along its course and covered grain size and organic matter, total N and P, sulfides, heavy metals, organochlorine, and pyrethroid pesticides. In addition, acute 10-day whole-sediment laboratory toxicity tests were carried with each sample, using the native amphipod Hyalella curvispina as test organism. In order to correlate both types of results, data were assessed by multivariate analysis, including principal component analysis (PCA). The physicochemical profile of samples resulted similar along the river course, though several anomalous data were registered in the middle course of the river, mainly in samples taken downstream a large industrial complex; with a few exceptions in upper basin sites characterized by the dominance of agricultural activities, the pesticides concentration were consistently below the analytical detection limits. Almost 50 % of the samples induced adverse effects on the amphipod when testing sublethal and lethal end points. The toxicity of the samples in terms of survival rate was extremely high in two sites, in particular in samples taken downstream the Pilar industrial complex. The integration of a selection of physicochemical and toxicological parameters of the sediments by PCA allowed discriminating areas of the river basin according the type and intensity of their particular pollution condition.